Religious Moderation in Multicultural Society: Guardians and Reinforcers of Moderate Understanding in the City of Pontianak - Abdurrahman, Abdurrahman; Sayadi, Wajidi (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
Pontianak City which is famous for its plurality is an interesting research location to study in terms of moderation because when other regions have conflicts due to differences but the city of Pontianak still remains harmonious and peaceful from split conflicts, therefore this study tries to reveal the parties that make religious moderation still exist and survive until now as well as activities conducted to strengthen community harmony in the city of Pontianak. The research method used is qualitative with an analytical descriptive approach which the data were collected by direct interviews and in-depth observation from informants which is the key to the existence of moderate ideas in Pontianak City.Â There are several parties who are the key to the existence and strengthen moderation in the city of Pontianak such as religious leaders, leaders or administrators of houses of worship, such as administrators of mosques, churches and temples or temples, city governments and intellectuals and academics,Â they maintain moderation through their respective duties and responsibilities and are more active in anticipating the possibility of disputes in the community.